Dynamic changes of gut and skin microbiota in pancreatic cancer-induced skin injury - Siqi Yao; Xi Yan; Hao Chen; Shibo Lei; Jing Huang; Ke Guo; Zheng Yu (BMC Microbiology)
Abstract Background Skin lesions can occur during the progression of pancreatic cancer. With growing attention on the gut-skin axis, these lesions may be linked to the microbiota. Microbiota play a crucial role in skin-related conditions, including hair loss and overall skin health. However, few studies have investigated the dynamic changes in gut and skin microbiota associated with skin lesions during cancer progression. In this study, 16S rRNA gene sequencing was used to investigate the dynamic changes of the gut microbiota in mice without non-depilation (Unepi) and depilation (Epi) after PAN02 cell injection. We also revealed the changes in skin microbiota of Unepi mice (Unepi_D) and Epi mice (Epi_D) after depilation. Results Our study found that the alpha diversity significantly increased in Unepi_D, indicating an imbalance in gut microbiota homeostasis. In the skin microbiota, certain genera such as Staphylococcus and Devosia were up-regulated, while others like Lactobacillus were down-regulated. Similarly, in the gut microbiota, Parasutterella was enriched, whereas Blautia showed reduced abundance. In the Epi group, the trend of increasing pathogenic bacteria and decreasing probiotics suggests a disrupted microbial environment that may contribute to skin injury through the gut–skin axis. These findings highlight potential microbial targets for diagnosis and therapeutic intervention in pancreatic cancer-associated skin complications. Conclusion Therefore, our findings provide new insights and references for the prevention and treatment of skin-related diseases in clinical practice. Specific gut and skin microbiota alterations may serve as potential biomarkers or therapeutic targets for managing skin complications in pancreatic cancer patients. Clinical trial number Not applicable.